Analisis Pesan Dakwah dalam Film Negeri 5 Menara (Pendekatan Semiotika) - Aviva Febianti, Yola; aliyya, Lisana shidqin; rohmah, Siti; afriansyah, Sahrul (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
This study aims to analyze the da'wah message contained in the film “Negeri 5 Menara” using a semiotic analysis approach. The movie, adapted from the novel by Ahmad Fuadi, tells the story of the journey of a teenager and his friends in an Islamic boarding school, and their efforts to achieve their dreams. Using semiotic theory, this study identifies and interprets various visual and narrative elements in the film, including dialog, symbols, characters, and settings, which play a role in delivering da'wah messages. The method used in this research is qualitative with an analytical descriptive approach. Data were collected through in-depth observation of the film, text analysis, and review of relevant literature. The results showed that the movie “Negeri 5 Menara” conveyed various da'wah messages, such as the importance of education, religious values, and fighting spirit in facing various challenges. In addition, the movie also reflects the social and cultural dynamics of Indonesian society, as well as the role of the media in spreading positive values. It is hoped that this research can contribute to the understanding of how movies as a da'wah media can influence audiences